Perilaku Konsumtif dalam Belanja Online Memasuki Era 5.0 dalam Perspektif Manajemen dan Nilai-Nilai Islam - Agustina, Latifah Agustina; Leni, Leni Kirani; Moh. Ilham; Novie Andriani Zakariya (UIN Mataram, 2023)
The development of the era of society 5.0 has changed the way consumers interact and shop through media. Online shopping is a favorite of the community to meet needs. Among college students, online shopping has become a daily habit and necessity. This research focused on the consumptive behavior of UIN Sunan Ampel Surabaya students with a management perspective and Islamic values. The method used involves collecting qualitative data through observation, interviews, and documentation, with descriptive data analysis, a method used to analyze data by describing or describing the collected data. The results of this study show that UIN Sunan Ampel Surabaya students consider online shopping as an informative, stable price, and flexible way to shop. Although from the point of view of management and Islamic values, their behavior tends not to be in accordance with needs because it prioritizes wants.Keywords: Consumer Behavior, Online Shopping, Management, Islamic Values.